Inferior vena cava ultrasound to guide decongestion in acute decompensated heart failure: a randomized controlled trial : heart failure - Jobs, Alexander; Rausch, Tanja K.; König, Inke R.; Vonthein, Reinhard; Devendra, Ashika; Schäfer, Jane; Nauck, Matthias; Eitel, Ingo; Stiermaier, Thomas; Laugwitz, Karl-Ludwig; Ledwoch, Jakob; Valentova, Miroslava; et al. (JACC Heart failure, 2025)
Background - Residual congestion at hospital discharge after an episode of acute decompensated heart failure (ADHF) is associated with poor prognosis. There is no consensus on how optimal decongestion should be assessed. - Objectives - This study aims to determine whether decongestive therapy guided by ultrasound measurements of inferior vena cava (IVC) diameters leads to greater reductions in N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels from baseline to hospital discharge as compared with decongestion treatment guided by clinical assessment alone. - Methods - In a randomized controlled multicenter trial, patients admitted for ADHF (NYHA functional class ≥III) exhibiting signs of pulmonary congestion, peripheral edema, and NT-proBNP levels >300 ng/L were randomized to either decongestion therapy guided by daily IVC ultrasound plus clinical assessment or clinical assessment alone. The primary endpoint was the change in NT-proBNP levels from baseline to discharge. - Results - A total of 388 patients were randomized, of which 327 were included in the primary intention-to-treat analysis. The between-group difference in primary endpoint of change in NT-proBNP levels was 5.4% (95% CI: −9.4% to 22.6%; P = 0.58). Safety events were numerically less frequent in the IVC ultrasound-guided group. No difference between groups was consistently observed in secondary endpoints with similar rates of hemoconcentration and intensity of diuretic treatment. - Conclusions - Additional ultrasound evaluation of IVC diameters did not improve decongestion treatment compared with clinical assessment alone among patients admitted for ADHF. (Ultrasound Evaluation of the IVC in Addition to Clinical Assessment to Guide Decongestion in ADHF [CAVA-ADHF-DZHK10]; NCT03140566).